(untitled) (Praxis Educativa, 2012)
This text refers to some results from the research work “Teachers who train teachers. Professional Development Fields” which was carried out at the Research Centre of the Philosophy and Humanities College of The National University of Cordoba (2008-2009). One of the most important aims of this research is to demonstrate that four-year teacher-training institutes in Cordoba have high academic standards comparable to those of a university. In other words, we would like to show the traces left by the University in the body, reasoning and practice of teachers who train other teachers. It is to be valued that academic and critical knowledge of subjects has been implemented in the ISFD, as well as the analysis of the limitations that this new approach brings about. Some queries are still to be answered: the clash between “academic legacy” and “teaching training sense”.